2021
DOI: 10.1002/bsd2.159
|View full text |Cite
|
Sign up to set email alerts
|

Country diagnostics for low carbon development: Can developing countries pursue simultaneous implementation of the Sustainable Development Goals and the Paris Agreement?

Abstract: The Sustainable Development Goals (SDGs) in the 2030 Development Agenda and the Paris Agreement, both agreed in 2015, call for the world to simultaneously address development and climate change. Some researchers argue that the SDGs put more emphasis on the value of economic growth, and if so, it would pose a challenging situation, especially to developing countries considering the nexus among economic growth, energy consumption, and CO2 emissions. In order to understand to what extent the SDGs advancement acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Policymakers must also incorporate the additional energy demand necessary to accomplish other SDGs and transformation toward decarbonisation [48,58]. Relevant to this issue, it is found that countries with tangible positive economic growth effects on their per capita CO2 emission made significant advancements in the SDGs, implying that embedding carbon in highly intensive sectors greatly impacts other sectors' carbon footprints [59]. Countries following 'low CO2 emission and high SDG attainment' development pathways or countries with strong agenda on well-being targets have a policy focus to facilitate investment that allows expansion of essential public services coverages, such as health, education, energy, water, and sanitation [23,34,59].…”
Section: Moving Forward: Rethinking Policy Change Frameworkmentioning
confidence: 99%
“…Policymakers must also incorporate the additional energy demand necessary to accomplish other SDGs and transformation toward decarbonisation [48,58]. Relevant to this issue, it is found that countries with tangible positive economic growth effects on their per capita CO2 emission made significant advancements in the SDGs, implying that embedding carbon in highly intensive sectors greatly impacts other sectors' carbon footprints [59]. Countries following 'low CO2 emission and high SDG attainment' development pathways or countries with strong agenda on well-being targets have a policy focus to facilitate investment that allows expansion of essential public services coverages, such as health, education, energy, water, and sanitation [23,34,59].…”
Section: Moving Forward: Rethinking Policy Change Frameworkmentioning
confidence: 99%
“…Healthcare systems must develop the ability to measure and use data to learn and must be based on four values: they must be for people and they must be equitable, resilient, and efficient [127]. Well-directed political institutions expanding essential public services such as healthcare, education, energy, water, and sanitation are effective in promoting the SDGs [128].…”
Section: Analysis Of the Sustainable Development Goals And Their Indimentioning
confidence: 99%
“…In any country or community, energy projects and installations of any type and in any field cannot be conceived without a remote management system, effective in promoting the SDGs [128].…”
mentioning
confidence: 99%
“…The literature on corporate involvement in development has discussed the nature, success, and sustainability implications of private sector involvement in SDGs via CSR (Haslam, 2021), internal audit and governance (Auld & Renckens, 2021), a role for accounting research (Bebbington & Unerman, 2018). Kobayakawa (2021) suggests that private sector involvement may be beneficial in keeping the increase in carbon emissions contained in specific sectors in line with the Paris agreement while the government implements the SDGs. Companies also use CSR to depress collective action by workers (Haslam, 2021) or contribute to development (Forcadell & Aracil, 2019).…”
Section: Implications For Using Mandatory Csr For Un Sdgsmentioning
confidence: 99%